O ciągłości celów wychowawczych i edukacyjnych – wyniki badań jakościowych przeprowadzonych na wychowawcach i nauczycielach przedmiotów w Izraelu - Bar Gosen, Noah (Studia Edukacyjne, 2020)
This research project presents different role perceptions regarding educational and academic aims, among high school instruction personnel. Since its foundation the Israeli education system has defined its role as a socialization agent as well as an academic institution. As national and international achievement tests became more widespread, the focus on academic aspect increased and the influence of academic excellence on school grading can be seen as more influential in comparison to educational achievements. Semi-structured interviews of 14 high school teachers – homeroom educators and subject teachers – were conducted. Results show that homeroom educators put more emphasis on educational aims while subject teachers put more emphasis on academic achievements. Their definition of success was a mixture of both objectives. Homeroom educators tend to apply educational inclusive practices while subject teachers tend to apply instructional ones. International research emphasizes the importance of educational aims and inclusive practices in promoting academic achievements for all (OECD, 2010). The emphasis on evaluation and assessment of academic achievements may results in exclusive practices. These results suggest that adding educational achievements to schools' evaluation scales can encourage all instruction personnel to promote educational aims and inclusive practices as well as academic ones, thus contributing to schools' performance in evaluation tests.